Experimental Measurements of Host Identity Protocol for Mobile Nodes' Networks. (4th August 2009) - Ben Jemaa, Maher; Abid, Nahla; Laurent-Maknavicius, Maryline; Chaouchi, Hakima
Abstract : The role of Internet Protocol (IP) is becoming more and more problematic especially with the new requirements of mobility and multihoming. Host Identity protocol (HIP) defines a new protocol between the network and transport layers in order to provide a better management to those requirements. The protocol defines a new namespace based on cryptographic identifiers which enable the IP address roles dissociation. Those new identifiers identify hosts rather than IP addresses. Because HIP is a quite recent protocol, we propose to present an experimental evaluation of its basic characteristics.